Monitoring hospital wastewaters for their probable genotoxicity - Beltifa, Asma; Alibi, Sana; Mansour, Hedi Ben (Journal of water and health, 2020)
Hospitals' effluents contain a considerable amount of chemicals. Considering the significant volume of wastewater discharged by hospitals, the presence of these chemicals represents a real threat to the environment and human health. Thus, the aim of this study was to evaluate the in vivo and in vitro genotoxicities of three wastewater effluents collected from Tunisian hospitals. The liver of Swiss albino male mice, previously treated with different doses of the hospital wastewaters, was used as a model to detect DNA fragmentation. Our results showed all the hospital effluents caused significant qualitative and quantitative hazards in hepatic DNA. The wastewater collected from Sfax hospital exhibited the highest genotoxic effect, which may be explained by the presence in this effluent of some toxic micropolluants. There was a significant increase in genotoxicity, proportionally to the concentration of effluent. However, the vitotox assay did not show any significant genotoxicity on Salmonella typhimurium TA104 in the presence or absence of microsomal fraction S9. The ratio gentox/cytox was lower than the threshold 1.5. This study assessed the toxicological risk issued from Tunisian hospital wastewaters, which is potentially very harmful, and it has been pointed out that wastewater treatment requires special attention.